SELF-CONSISTENT CALCULATIONS OF WORK FUNCTION, SHOTTKY BARRIER HEIGHTS AND SURFACE ENERGY OF METAL NANOFILMS IN DIELECTRIC CONFINEMENT - Babich, A. V.; Pogosov, V. V.; Vakula, P. V. (Radio Electronics, Computer Science, Control, 2013)
We suggest a method for the self-consistent calculations of characteristics of metal films in dielectric environment. Within a modified Kohn-Sham method and stabilized jellium model, the most interesting case of asymmetric metal-dielectric sandwiches is considered, for which dielectric media are different from the two sides of the film. As an example, we focus on Na, Al and Pb. We calculate the spectrum, electron work function, and surface energy of polycrystalline and crystalline films placed into passive isolators. We find that a dielectric environment generally leads to the decrease of both the electron work function and surface energy. It is revealed that the change of the work function is determined only by the average of dielectric constants from both sides of the film. We introduced the position of a conductivity band in the dielectric as a parameter in the self-consistency procedure and performed calculations, using image potential, for the aluminum film with ideal interfaces vacuum/Al(111)/SiO 2 , vacuum/Al(111)/AlO and sandwiches SiO/Al(111)/AlO. As a result, effective potential profiles and the Schottky barrier heights were calculated.